BURN INJURY: GENERAL CONCEPTS AND INVESTIGATION BASED ON ANTEMORTEM AND POSTMORTEM OF CLINICAL INJURY - Yulia Ratna Sintia Dewi (Universitas Udayana, 2013)
Burn injury is a condition which catastrophic consequences can affect the suffererphysically, socially, as well as financially. Medicolegal aspect of a burn requiresphysicians to be able to examine burn injuries on both the living and the dead.Burn injury is defined as tissue damage due to contact with dry heat (fire), humidheat (vapor or hot liquid), chemicals (corrosive agents), electrical devices (lamp orelectrical current), friction, as well as electromagnetic energy. Burn can beclassified according to its breadth and degree. Death by burn injuries can beclassified into 2 categories which are slow death and the fast one. The differencebetween antemortem and postmortem burn injury is that antemortem injury willshow several intravital signs in the bullae and vesicles while postmortem injurywill have none.Three main points exist in identifying antemortem and postmortemburn injuries, namely redness lines, vesication, and reparative processes.